(3JMaI Gdedhcs - (3YeQ Hf eMeO Hf CMeO Hf ESeGYjd, CHh MaU, fLe GdOjf GdfSaj,J (B537 (3g` s ((3YHO GdcQje Hf GdSjO ejQZfi GdMSjfi GdHNGQi s)
(3ChdgG (B:s
(3jHOC HcJGH GdWgGQI s
(3BNQgG (B:s
(3aYdjc jG CNj HGdJbhi hGdESJYOGO hedGReI GdUHQ hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B306 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B783s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg TGaYi (B1156) s
Keywords: (3Gdabg GdMfajs